2019
DOI: 10.1111/jbi.13698
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting scales of local persistence between monsoonal and arid biomes in closely related, low‐dispersal vertebrates

Abstract: Aim Focussing on pairs of sister species across three genera of scincid lizards, we use genomic evidence to test for larger‐scale, late‐Pleistocene changes in distributions of lizards in the Australian arid zone (AZ) than in the adjacent monsoonal tropics (MT). Location Northern and central Australia. Taxon Scincidae: Squamata. Methods We sequenced ~2000 nuclear exons and one mitochondrial gene across the distributions of species with primarily MT or AZ distributions from three genera of lizards. Using phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…This phenomenon has been observed previously in species pairs in which one is confined to the wet zone while the other is distributed across the dry zone, such as Devario micronema vs D. malabaricus, Laubuka varuna vs. L. lankensis, Systomus pleurotaenia vs S. sarana, and Rasbora wilpita vs R. dandia [11,14,15,39]. As Potter et al [52] show, genetic diversity in low-dispersal vertebrate species tends to be higher in mesic, topographically complex biomes, compared to that of species inhabiting dry and topographically less complex biomes.…”
Section: Phylogeographysupporting
confidence: 77%
“…This phenomenon has been observed previously in species pairs in which one is confined to the wet zone while the other is distributed across the dry zone, such as Devario micronema vs D. malabaricus, Laubuka varuna vs. L. lankensis, Systomus pleurotaenia vs S. sarana, and Rasbora wilpita vs R. dandia [11,14,15,39]. As Potter et al [52] show, genetic diversity in low-dispersal vertebrate species tends to be higher in mesic, topographically complex biomes, compared to that of species inhabiting dry and topographically less complex biomes.…”
Section: Phylogeographysupporting
confidence: 77%
“…However, some studies have found significantly lower genetic diversity in this mesic upland compared to other areas of the arid zone (Laver et al., 2017; Melville et al., 2016; Oliver, Couper, et al., 2014; Pepper, Doughty, et al., 2011), much more indicative of recent recolonization than of long‐term persistence. In addition, the hypothesis that arid adapted lineages exhibit wider distributions and shallower divergences than their Monsoon Tropics counterparts, potentially a result of large‐scale expansions following relative climatic amelioration during interglacials has been supported by a number of studies (Anderson et al., 2016; Fujita et al., 2010; Jennings et al., 2003; Laver et al., 2017; Oliver & Bauer, 2011; Oliver, Couper, et al., 2014; Pepper, Ho, et al., 2011; Potter et al., 2019). However, taxa such as cf.…”
Section: The Evolution Of Arid Zone Biodiversitymentioning
confidence: 90%
“…However, for many other species these empty sand‐coloured patches on the map represent a frustrating gap in knowledge, particularly given the phylogenetic picture emerging from other better‐sampled parts of the arid zone. While in general the patterns appear to lack the deeply divergent and geographically localized endemism typified in taxa across the adjacent Monsoon Tropics (Fujita et al., 2010; Moritz et al., 2016; Noble et al., 2017; Potter et al., 2019), all show significant genetic variation across the arid zone (see Figure 3). This includes topographically flat areas of low‐lying desert where there are no obvious barriers to dispersal and gene flow.…”
Section: The Evolution Of Arid Zone Biodiversitymentioning
confidence: 97%
See 2 more Smart Citations